2011
DOI: 10.1016/j.pnpbp.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate proton spectroscopy glutamate levels differ as a function of smoking cessation outcome

Abstract: Background Cigarette smoking is the leading preventable cause of death. Unfortunately, the majority of smokers who attempt to quit smoking relapse within weeks. Abnormal dorsal anterior cingulate cortex (dACC) function may contribute to tobacco smoking relapse vulnerability. Growing evidence suggests that glutamate neurotransmission is involved in mediating nicotine dependence. We hypothesized that prior to a cessation attempt, dACC glutamate levels would be lower in relapse vulnerable smokers. Methods Proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
0
25
4
Order By: Relevance
“…They also did not find group difference on brain CHO between smokers and non-smokers. Contrary to this study and to our study of young children with PNE, another preliminary study of nine women who participated in a smoking cessation program found that those who “slipped” and resumed smoking had lower brain glutamate/tCr level in the ACC, but also normal NAA level, compared to those who remained abstinent (Mashhoon et al 2011). Given the small sample size of these studies and the difference in the developing brain of young children compared to the matured adult brain, the effects of nicotine on neurometabolites are not comparable between these populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They also did not find group difference on brain CHO between smokers and non-smokers. Contrary to this study and to our study of young children with PNE, another preliminary study of nine women who participated in a smoking cessation program found that those who “slipped” and resumed smoking had lower brain glutamate/tCr level in the ACC, but also normal NAA level, compared to those who remained abstinent (Mashhoon et al 2011). Given the small sample size of these studies and the difference in the developing brain of young children compared to the matured adult brain, the effects of nicotine on neurometabolites are not comparable between these populations.…”
Section: Discussioncontrasting
confidence: 99%
“…However, unlike the children with prenatal methamphetamine exposure (Chang et al 2009), our children with PNE did not show higher levels of neuronal marker NAA, but had trends for lower levels in the thalamus and the basal ganglia. NAA was found to be lower in the frontal white matter of adult smokers who were also recovering alcoholics (Wang et al 2009) but not in the other studies of adult men or women smokers (Mason et al 2006; Mashhoon et al 2011). Therefore, our findings are consistent with studies that found no evidence of neuronal loss (cell numbers in adult rats) in hippocampus or cerebellum after exposed to nicotine prenatally or both prenatally and postnatally (Chen et al 2006).…”
Section: Discussioncontrasting
confidence: 60%
“…Our prior work suggests that a relationship exists between dACC Glu and treatment outcome as individuals who are more likely to relapse have reduced dACC Glu (Mashhoon et al, 2011). These findings are somewhat in contrast to our current work, which suggests higher dACC Glu enhances self-relevant processing of smoking cues, which could be considered a risk factor for relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the present study did not control for the genetic background, eg, variation in the NMDA 2B receptor gene (GRIN2B), which has been shown to influence ACC Glx concentration (Arnold et al, 2009). Also, smoking or smoking cessation impacting anterior cingulate proton spectroscopy glutamate levels were not considered as potentially confounding factors (Mashhoon et al, 2011).…”
Section: Discussionmentioning
confidence: 99%